Effect of hysteroscopic septum resection on preterm delivery rate in singleton pregnancies. Issue 6 (1st December 2021) - Miklavcic, Jana; Laganà, Antonio Simone; Premru Srsen, Tanja; Korosec, Sara; Ban Frangež, Helena
Abstract: Introduction: Uterine septum is the most common uterine anomaly and is often found during the work-up in primary infertile women. In this study, we aimed to evaluate the potential effect of hysteroscopic septum resection (HSR) on preterm delivery (PTD) in primary infertile women who had singleton pregnancies. Material and methods: We analyzed 420 singleton pregnancies after primary infertility treatment and compared the PTD rates in women who underwent previous HSR (cases) and women who did not undergo previous operative hysteroscopy or cervical dilation (controls), regardless of the modality of conception (spontaneous or by in vitro fertilization). Results: We did not find significant differences between cases and controls for the incidence of overall PTD rate ( p = .237), PTD before 32 gestational weeks ( p = .848), and between 32 and 37 gestational weeks ( p = .324), premature rupture of membranes ( p = .419), and neonatal birth weight ( p = .129). Overall, the risk of spontaneous PTD <37 gestational weeks after HSR was not found to be significantly higher compared to controls (RR 1.29, 0.61–2.73 95% CI; p = .561). Conclusion: According to our results, previous HSR could be not considered a risk factor for PTD in singleton pregnancies, regardless of the modality of conception (spontaneous or by in vitro fertilization).